Integral equation approximation to microwave specific attenuation by distorted raindrops: the Pruppacher-and-Pitter model - Li, L.W. (2014)
Proceedings of IEEE Singapore International Conference on Networks/International Conference on Information Engineering IEEE SICON/ICIE